OPTIMASI PERENCANAAN PENGGUNAAN LAHAN SAWAH BARU DALAM MENDUKUNG KETAHANAN PANGAN DI KABUPATEN MAROS, SULAWESI SELATAN - Munawir; Wahab, Nurhikmah (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2026)
Paddy field conversion in Maros Regency during the 2013–2023 period reached 1,946 hectares, equivalent to approximately 0.7% per year, and has led to a food balance deficit since 2023. This study aims to optimize the planning of new paddy fields to support food security in Maros Regency through: (1) identification of land availability, (2) land suitability analysis, (3) determining priority allocation areas, and (4) establishing the optimal allocation of new paddy field development. Data on available land were obtained through visual interpretation of Spot 5 Satellite Imagery (2025), field surveys, and spatial analysis. Land suitability analysis for paddy fields was conducted using the criteria of BRMP-SDLP and the Multicriteria Evaluation (MCE) method. Priority allocation was determined using Spatial Multicriteria Decision Making (SMCDM). Optimal allocation was generated using a Goal Programming model with the Weighted Goal Programming (WGP) method. The results show that satellite image interpretation achieved high accuracy, with a Kappa coefficient of 92.0%. A total of 31,922 hectares of land were identified as available for new paddy field development, consisting of 1% highly suitable (S1), 26% moderately suitable (S2), 11% marginally suitable (S3), and 61% not suitable (N), with slope and soil texture as the main constraining factors. Priority areas were divided into Priority 1 (11,761 ha) and Priority 2 (20,161 ha). Simulation of four allocation scenarios (2,500 ha, 5,000 ha, 7,500 ha, and 10,000 ha) indicates that the 10,000-ha scenario yields the smallest goal function value, suggesting a more efficient and balanced distribution of land allocation.